Fractalkine induces angiogenic potential in CX3CR1-expressing monocytes. Issue 1 (28th December 2017) - Park, Youngrok; Lee, Joon; Kwak, Jae-Yong; Noh, Kyoungmi; Yim, Eunjung; Kim, Hyun-Kyung; Kim, Young June; Broxmeyer, Hal E; Kim, Jeong-A
Abstract: We report the unique role of CX3CL1 (or fractalkine) on CD11b + myelomonocytic cells expressing CX3CR1, the only known receptor for CX3CL1, in promoting blood perfusion recovery. In a mouse ischemic hind-limb model, CD11b + CX3CR1 + cells migrated to ischemic femoral muscles through CX3CL1-mediated chemotaxis. CD11b + CX3CR1 + macrophages isolated from ischemic tissues [tissue (T)-CD11b + CX3CR1 + ] of muscle exert a proangiogenic effect through platelet factor-4 (CXCL4; PF-4) production. PF-4 does not promote angiogenesis by itself but, instead, increases VEGF-mediated angiogenesis. Despite proangiogenic effects of muscle-derived T-CD11b + CX3CR1 + macrophages, their clinical implementation is limited because muscle excision is required for cell harvesting. Therefore, we focused on the more accessible bone marrow (BM)-CD11b + CX3CR1 + monocytes, which migrate from BM into ischemic muscles via CX3CL1-mediated chemotaxis. PF-4 expression was not detected in BM-CD11b + CX3CR1 + monocytes under normal conditions, but CX3CL1 (50 ng/ml) induced high PF-4 expression and enabled BM-CD11b + CX3CR1 + monocytes to achieve a similar angiogenic potential to that of T-CD11b + CX3CR1 + macrophages ex vivo. Furthermore, we were able to identify a subset of monocytes that express CD11b and CX3CR1 in human peripheral blood and confirmed the proangiogenic effect of CX3CL1 treatment. Thus, CX3CL1-treated CD11b + CX3CR1 + monocytes may be of potential therapeutic use to significantly accelerate recovery of blood perfusion in ischemic diseases.